Calibrated ages of Cayambe-Coca (core C5) peat core from Ecuador - John Hribjlan (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.